2018
DOI: 10.1155/2018/7413027
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Heparanase Suppresses Invasion of Human Trophoblasts by Activating p38 MAPK Signaling Pathway

Abstract: Preeclampsia is a pregnancy-related disease with increasing maternal and perinatal morbidity and mortality worldwide. Defective trophoblast invasion is considered to be a major factor in the pathophysiological mechanism of preeclampsia. Heparanase, the only endo-β-glucuronidase in mammalian cells, has been shown to be abnormally expressed in the placenta of preeclampsia patients in our previous study. The biological role and potential mechanism of heparanase in trophoblasts remain unclear. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…For example, a study by Zhou et al [ 20 ] has revealed that transforming growth factor- β 1 could inhibit the apoptosis of trophoblasts induced by mercuric chlorides by suppressing the p38MAPK signaling pathway, and one other study by Ebegboni et al [ 21 ] also reported that flavonoids promoted the self-renewal and invasion of spherical stem cells of trophoblasts by inhibiting p38MAPK signaling pathway. In addition, one study by Che et al [ 22 ] also found that knockout of heparanase gene inhibits the invasion of human trophoblasts by activating the p38MAPK signaling pathway. Heparin has also been reported to inhibit excessive circulation and remodeling of porcine pulmonary artery via the p38MAPK signaling pathway, thus alleviating the pulmonary hypertension [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Zhou et al [ 20 ] has revealed that transforming growth factor- β 1 could inhibit the apoptosis of trophoblasts induced by mercuric chlorides by suppressing the p38MAPK signaling pathway, and one other study by Ebegboni et al [ 21 ] also reported that flavonoids promoted the self-renewal and invasion of spherical stem cells of trophoblasts by inhibiting p38MAPK signaling pathway. In addition, one study by Che et al [ 22 ] also found that knockout of heparanase gene inhibits the invasion of human trophoblasts by activating the p38MAPK signaling pathway. Heparin has also been reported to inhibit excessive circulation and remodeling of porcine pulmonary artery via the p38MAPK signaling pathway, thus alleviating the pulmonary hypertension [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAPK, including JNK, ERK, and p38 kinase, plays pivotal roles in proliferation, invasion, and migration of cancer cells[ 33 - 36 ]. There are many studies[ 37 - 39 ] that have shown that H. pylori infection leads to increased p38MAPK in GC cells, and it has also been shown[ 40 ] that p38MAPK leads to HPA elevation. This study showed that HPA and MAPK expression was significantly higher in patients with GC than that in para-carcinoma and normal gastric tissues.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies[ 37 - 39 ] showing that H. pylori infection leads to increased p38MAPK in GC cells, and it has been shown that[ 40 ] p38MAPK leads to elevation of HPA. Therefore, we hypothesized that H. pylori infection causes an increase in HPA in GC via the MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…C-type lectin receptors are expressed mainly on myeloid cells and are involved in antifungal immunity. The MAPK signaling pathway is vital in the mediation of multiple cellular processes, which include proliferation, stress response, differentiation, motility, survival, growth, and death [29]. The PI3K-Akt signaling pathway plays a vital role in mediating survival signals in different types of neuronal cells.…”
Section: Discussionmentioning
confidence: 99%